THE USE OF CODE-MIXING BY THE CASTER IN PUBG MOBILE TOURNAMENT â€œPMPL SEA FINALS SEASON 2â€ - Abdul Rozzaq Wijaya, Rahmaditya Khadifa; Hidayatullah, Aris; Mayangseto, Ginarsiwi (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
This study aims to determine the types of code mixing and the factors that cause code mixing. The data in this study are the types of code mixing Inter Sentential Code Mixing and Inter Lexical Code Mixing. The source of the data in this study was the PUBG Mobile e-sport tournament video with the title "PMPL SEA FINALS SEASON 2" taken from the research location of the PUBG MOBILE INDONESIA Youtube channel. This research is descriptive qualitative. Data collection techniques in this study used observing (simak) and note-taking (catat) techniques. In addition, the data analysis technique in this study uses theory from Hoffman (1991) and Jendra (2007). The result of this study is that the use of code mixing by the caster found Inter Sentential Code Mixing in the form of phrases and clauses. Then, the type of Inter Lexical Code Mixing code mixing is found in the form of words. The factors found in this study: (1) the language factor, (2) the speech participant factor, and (3) the purpose of the conversation factor.